2008
DOI: 10.7547/0980445
|View full text |Cite
|
Sign up to set email alerts
|

Application of Cantharidin and Podophyllotoxin for the Treatment of Plantar Warts

Abstract: A topical solution of cantharidin, podophyllotoxin, and salicylic acid was found to be safe and effective in the treatment of simple and mosaic plantar warts. This formulation is a promising alternative treatment modality for plantar warts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 10 publications
0
18
1
Order By: Relevance
“…Combination treatments can be undertaken 10,17,20,21 Other treatments: dithranol, 87 5-FU, 93 formaldehyde, 78 glutaraldehyde, 35 hyperthermia, 55 laser, 58,65 PDT, 68,73 podophyllotoxin, 90 topical immunotherapy 133,136 Plane warts On the backs of the hands or face, plane warts are mainly a cosmetic problem and spontaneous clearance can often be awaited. Destructive and caustic agents are more likely to produce scarring at these sites and should be used with care Salicylic acid cream/ointment 2-10% or cautious use of salicylic acid paint, 12-17%, used without occlusion Cryotherapy, milder freeze Topical retinoid 110,111 Others treatments: acupuncture, 171 cantharidin, 41 for the most part, weak.…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Combination treatments can be undertaken 10,17,20,21 Other treatments: dithranol, 87 5-FU, 93 formaldehyde, 78 glutaraldehyde, 35 hyperthermia, 55 laser, 58,65 PDT, 68,73 podophyllotoxin, 90 topical immunotherapy 133,136 Plane warts On the backs of the hands or face, plane warts are mainly a cosmetic problem and spontaneous clearance can often be awaited. Destructive and caustic agents are more likely to produce scarring at these sites and should be used with care Salicylic acid cream/ointment 2-10% or cautious use of salicylic acid paint, 12-17%, used without occlusion Cryotherapy, milder freeze Topical retinoid 110,111 Others treatments: acupuncture, 171 cantharidin, 41 for the most part, weak.…”
Section: Future Directionsmentioning
confidence: 99%
“…However, application was complex, and blistering and pain could result. 21 8.2.1.b. Cryotherapy (level of evidence 1+; strength of recommendation B).…”
mentioning
confidence: 99%
“…There are few controlled studies that focus specifically on the treatment of warts, and even fewer studies exist on the treatment of plantar warts 2–6 . It has recently been reported that the topical proprietary formulation consisting of 1% cantharidin, 5% podophyllotoxin, and 30% salicylic acid (CPS) has achieved complete clearance of plantar warts in 95.8% of patients 7 . This is a high cure rate compared to other treatments 3–5 .…”
Section: Introductionmentioning
confidence: 99%
“…Combination therapy of cantharidin 1%, salicylic acid 30%, and podophyllotoxin 5% with subsequent debridement has shown a 96% cure rate for plantar warts with most patients requiring only one treatment [7]. …”
Section: Destructive Therapymentioning
confidence: 99%